AB1245 COMPARATIVE ANALYSIS OF SPONTANEOUS INFECTIOUS SPONDYLITIS: PYOGENIC VERSUS BRUCELLA. (June 2019) - Ammar, Lobna Ben; Tekaya, Aicha Ben; Tekaya, Rawdha; Saidane, Olfa; Hammamia, Mohammed Ben; Mahmoud, Ines; Abdelmoula, Leila
Abstract : Background: Infectious spondylitis is an infectious disease of the spine or paraspinal structures that can be caused by various microorganisms. Without adequate chemotherapy, the outcome can be fatal or result in severe neurologic damage. Therefore, differentiating the etiology of spondylitis is very important. Objectives: To compare the clinical features, laboratory and radiological aspects, treatment and outcome data of patients diagnosed as brucellar spondylitis (BSP) and pyogenic spondylitis (PSP). Methods: Retrospective study including 45 (22 BSP and 23 PSP) spondylodiscitis hospitalized in our department between 1999 and 2019. The diagnosis was based on clinical, biological, radiological and bacteriological data. Results: The patients' mean age was 54 years. There were 31 men (68.8%) and 14 women (31.2%). There was no difference in mean age and sex between the two groups (p=0.8 and p=0.4; respectively). The pyogenic group had a relatively higher proportion of Predisposing factors especially diabeties (p=0.04). PSD patients suffered an impaired general condition more frequently than BSD patients (p=0.01) while BSD patients complained of night sweats more frequently compared to PSD cases (p=0.026). The peak CRP value was higher in the pyogenic group than in the brucella group (87 mg/L and 37 mg/L, respectively, p=0.027), whereas the ESR was not significantly different between the groups (71 mm/h and 67 mm/h, respectively, p=0.7). We found no statistically significant difference regarding the seat of the spondylitis. Whereas, multifocal involvement was higher in PSD (p=0.049). Radiologically, the frequency of prevertebral, paravertebral, epidural, and psoas abscess formations and spinal cord compression was similar in both groups (p=0.8) Surgical interventions and percutaneous sampling and/or abscess drainage were applied more frequently in PSD but with no significant difference (p<0.23). Favourable clinical outcome rate was 60% in PSD and it was 72% in BSD group (p=0.39). Conclusion: The clinical and radiological manifestations of spontaneous spondylitis differ based on the causative organism. Pyogenic spondylitis patients tend to have a more severe clinical course and a higher CRP level. However, there was no significant difference regarding the presence of abscess and epiduritis or the occurrence of complications between brucella and pyogenic spondilitis. Disclosure of Interests: None declared